2016
DOI: 10.1542/peds.2016-0256
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Continuity During Transfer to Adult Care: A Systematic Review

Abstract: CONTEXT: Appropriate outcomes are required to evaluate transition programs' ability to maintain care continuity during the transfer to adult care of youths with a chronic condition. OBJECTIVE:To identify the outcomes used to measure care continuity during transfer, and to analyze current evidence regarding the efficacy of transition programs.DATA SOURCES: PubMed (1948PubMed ( -2014, Web of Science (1945, Embase (1947Embase ( -2014, and the reference lists of the studies identified. STUDY SELECTION:Screening on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…This population of emerging adults then faces the challenge of transitioning from the pediatric to adult diabetes care setting, often at the same time as other major life changes including independent living, starting undergraduate studies or joining the workforce for the first time, changes in health insurance, and potentially starting a family of his or her own. Several recent publications have noted the lack of evidence-based strategies for transition of emerging adults with a variety of chronic medical conditions (2)(3)(4). In particular, managing the transition of young adults with T1DM has led to more discussion and research in this important area.…”
Section: Introductionmentioning
confidence: 99%
“…This population of emerging adults then faces the challenge of transitioning from the pediatric to adult diabetes care setting, often at the same time as other major life changes including independent living, starting undergraduate studies or joining the workforce for the first time, changes in health insurance, and potentially starting a family of his or her own. Several recent publications have noted the lack of evidence-based strategies for transition of emerging adults with a variety of chronic medical conditions (2)(3)(4). In particular, managing the transition of young adults with T1DM has led to more discussion and research in this important area.…”
Section: Introductionmentioning
confidence: 99%
“…Poor compliance to these agents may not just be fear of needles, but reluctance of difficulties with self-administration, that my lead to social isolation. 25,31,33,34 Daedalus promotes self-education The patient's recognition of the triggering episodic crises and any experience of non-drug compliance will experientially help him/her realize the consequences of disobedience. Typical triggers, such as heat and overuse for FMF or cold exposure to cryopyrin syndromes need to be emphasized since diagnosis and may stimulate the patient to avoid or properly manage them.…”
Section: Avoiding Barriers Of a Successful Transition (The Waves)mentioning
confidence: 99%
“…In case of unraveled difficulties, individualized interactive training will be performed in the missing targets and the transition plan respectively modified or the final transfer delayed. 25,31,33,37 Moreover, recording questionnaires by the adolescent's response and aiming to evaluate his/her Satisfaction of the applied Health Service may support adherence to the Outpatient Clinic and promote his/her unprovoked preparation. 33,34,44,45 Daedalus and Icarus fly in parallel over the life waves and not too close to the inflammatory beams Upon verification of the patient's (and family's) global Transition readiness and absence of any disease flare or other physical or emotional stress, the final and orchestrated transfer by the Transition team will be conducted.…”
Section: Avoiding Barriers Of a Successful Transition (The Waves)mentioning
confidence: 99%
See 1 more Smart Citation
“…8 A Cochrane review in 2016 found only four valid studies with a total of 238 participants -too few to draw conclusions. 9 The goals for transition are rarely made explicit but three factors seem critical. 10 First, provide youth with developmentally appropriate education about their epilepsy, clinical course and treatment.…”
Section: Introductionmentioning
confidence: 99%